Astragalus saponins and its main constituents ameliorate ductular reaction and liver fibrosis in a mouse model of DDC-induced cholestatic liver disease - Zhang, Linzhang; Hu, Yonghong; Qi, Shenglan; Zhang, Congcong; Zhou, Qun; Zhang, Dingqi; Mu, Yongping; Zhang, Hua; Chen, Gaofeng; Liu, Ping; Chen, Jiamei; Liu, Wei (Frontiers in Pharmacology, 2022)
Cholestatic liver disease (CLD) is a chronic liver disease characterized by ductular reaction, inflammation and fibrosis. As there are no effective chemical or biological drugs now, majority of CLD patients eventually require liver transplantation. Astragali radix (AR) is commonly used in the clinical treatment of cholestatic liver disease and its related liver fibrosis in traditional Chinese medicine, however its specific active constituents are not clear. Total astragalus saponins (ASTs) were considered to be the main active components of AR. The aim of this study is to investigate the improvement effects of the total astragalus saponins (ASTs) and its main constituents in cholestatic liver disease. The ASTs from AR was prepared by macroporous resin, the content of saponins was measured at 60.19±1.68%. The ameliorative effects of ASTs (14, 28, 56 mg/kg) were evaluated by 3, 5-Diethoxycarbonyl-1, 4-dihydrocollidine (DDC)-induced CLD mouse model. The contents of hydroxyproline (Hyp), the mRNA and protein expression of cytokeratin 19 (CK19) and α-smooth muscle actin (α-SMA) in liver tissue were dose-dependently improved after treatment for ASTs. 45 astragalus saponins were identified in ASTs by UHPLC-Q-Exactive Orbitrap HRMS, including astragaloside I, astragaloside II, astragaloside III, astragaloside IV, isoastragaloside I, isoastragaloside II, cycloastragenol, etc. And, it was found that ductular reaction in sodium butyrate-induced WB-F344 cell model were obviously inhibited by these main constituents. Finally, the improvement effects of astragaloside I, astragaloside II, astragaloside IV and cycloastragenol (50 mg/kg) were evaluated in DDC-induced CLD mice model. The results showed that astragaloside I and cycloastragenol significantly improved mRNA and protein expression of CK19 and α-SMA in liver tissue. It suggested that astragaloside I and cycloastragenol could alleviate ductular reaction and liver fibrosis. In summary, this study revealed that ASTs could significantly inhibit ductular reaction and liver fibrosis, and astragaloside I and cycloastragenol were the key substances of ASTs for treating cholestatic liver disease.